Seam or swing? Identifying the most effective type of bowling variation for fast bowlers in men's international 50-over cricket. Issue 14 (18th July 2022) - Mehta, Saumya; Phatak, Ashwin; Memmert, Daniel; Kerruish, Samuel; Jamil, Mikael
ABSTRACT: In this study, 13, 176 balls bowled by international level fast bowlers were analysed in order to investigate the relationship between the types of delivery and their effectiveness. The results of Chi-Squared analyses revealed significant associations between the type of delivery and runs conceded (p < 0.001) as well as wickets taken (p < 0.001). Seam movement was revealed to be more effective than swing bowling at both producing dot balls and taking wickets. Specifically, balls that 'seam-away" were revealed to be the most effective for bowling dots and "seam-in" for taking wickets. The "away-swinger" resulted in significantly greater than expected dot balls as did the "in-swinger" but only the in-swinger resulted in significantly greater than expected wickets. Both the "off-cutter" and "slower-balls" were revealed to result in significantly fewer than expected dot balls but significantly greater than expected wickets, implying bowlers must assess for themselves the risk versus reward of these two types of variation. Balls with no-movement were revealed to have no significant relationship with runs conceded, but did result in significantly fewer than expected wickets. Evidence suggests that lateral movement is crucial to bowling success with seam movement revealed to be more effective than swing.